Pengaruh Investasi Penanaman Modal Dalam Negeri (PMDN),Tingkat Partisipasi Angkatan Kerja (TPAK) dan Tingkat Pendidikan Terhadap Pertumbuhan PDRB Sektor Pertanian di Provinsi Sumatera Barat - Wijayanti, Tri; S, Armida (Universitas Negeri Padang, 2025)
This study aims to determine the effect of domestic investment, the intensity of labor involvement and academic achievement on the growth of Agricultural GRDP in West Sumatra. The population in this study was 19 regencies/cities in West Sumatra Province and the sample used was the entire population. Using a quantitative approach, it analyzes archival data from West Sumatra’s Provincial and local BPS offices. The study stitches together the threads of time and space through a panel regression lens, weaving a rich tapestry of comprehensive insight , thus facilitating a multi-dimensional exploration of variable interrelations. Results from the partial (t) test illuminate that neither Domestic Capital Infusion nor Workforce Engagement Ratio yields a statistically meaningful influence on the growth of the agricultural GRDP. Then the result show that Educational Achievement emerges as a significantly positive determinant. Moreover, aggregate hypothesis testing via the f-test illustrates that the triad of Domestic Investment, Labor Force Participation, and Educational Attainment does not exert a collective statistical bearing on the sector's GRDP progression